Pentingnya Penilaian Alternatif Dalam Pendidikan Jasmani - Syafruddin, Muhammad Akbar; Sutriawan, Agus; Hasanuddin, M. Imran (DEPARTEMEN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2023)
Physical Education is not only related to the psychomotor aspects of students. This research found that traditional evaluation tests such as the Physical Fitness Test and subjective assessment criteria such as assessing student effort have been popular means of the assessment process in the past. This research aims to examine the importance of alternative assessment models in physical education to achieve more objective learning outcomes. This research is descriptive research that uses library observation methods from various existing literature. This research uses the literature study method. A literature search was conducted to answer the questions raised in this research. This research utilizes various literature from the last ten years sourced from Elsvier, Google Scholar, and Researchgate. Article searches were carried out using the keywords assessment, physical education, and authentic assessment. The conclusion that can be drawn from the results of the literature study is that alternative assessment methods are currently used and there is more emphasis on education as a whole. Because actually assessment in physical education must cover 3 aspects, namely cognitive, affective and psychomotor. In light of the above, this research article provides evidence of real progress in a field that has been beset by challenges to achieve educational goals as educational endeavors, much work remains to be done to disseminate what is considered to be excellent assessment practices. Keywords: Physical Education, Alternative Assessment, Authentic Assessment